A revision on the generic status of three species of the genus Chacella Bruce, 1986 described by Li & Poupin (2009) (Crustacea: Decapoda: Palaemonidae) - Marin, Ivan (Zootaxa, 2010)
The pontoniine genus Chacella Bruce, 1986 was designated for Dasycaris kerstitchi (Wicksten, 1983) from Sonora, Mexico, the Eastern Pacific. Later, two newly described species, C. tricornuta Hendrickx, 1990 and C. mclaughlinae Li, 2006 were added to the genus (Hendrickx, 1990; Li, 2006). Recently revised (Marin, 2009) the genus became monotypic again with single species, C. kerstitchi (Wicksten, 1983), while two remaining species were transferred to newly designated genus Sandyella Marin, 2009 which can be distinguished by the dorsal ornamentation of the carapace (see Marin, 2009).